The MeteoMet2 project—highlights and results. (18th January 2018) - Merlone, A; Sanna, F; Beges, G; Bell, S; Beltramino, G; Bojkovski, J; Brunet, M; del Campo, D; Castrillo, A; Chiodo, N; Colli, M; Coppa, G; et al.
Abstract: Launched in 2011 within the European Metrology Research Programme (EMRP) of EURAMET, the joint research project 'MeteoMet'—Metrology for Meteorology—is the largest EMRP consortium; national metrology institutes, universities, meteorological and climate agencies, research institutes, collaborators and manufacturers are working together, developing new metrological techniques, as well as improving existing ones, for use in meteorological observations and climate records. The project focuses on humidity in the upper and surface atmosphere, air temperature, surface and deep-sea temperatures, soil moisture, salinity, permafrost temperature, precipitation, and the snow albedo effect on air temperature. All tasks are performed using a rigorous metrological approach and include the design and study of new sensors, new calibration facilities, the investigation of sensor characteristics, improved techniques for measurements of essential climate variables with uncertainty evaluation, traceability, laboratory proficiency and the inclusion of field influencing parameters, long-lasting measurements, and campaigns in remote and extreme areas. The vision for MeteoMet is to take a step further towards establishing full data comparability, coherency, consistency, and long-term continuity, through a comprehensive evaluation of the measurement uncertainties for the quantities involved in the global climate observing systems and the derived observations. The improvement in quality of essential climate variables records, through the inclusion of measurement uncertainty budgets, will also highlight possible strategies for the reduction of the uncertainty. This contribution presents selected highlights of the MeteoMet project and reviews the main ongoing activities, tasks and deliverables, with a view to its possible future evolution and extended impact.